Pengaruh Penggunaan Media Permainan Engklek Terhadap Hasil Belajar Peserta Didik Materi Sistem Organisasi Kehidupan Kelas Vii Smpn 15 Bulukumba : The Influence of the Use of Engklek Game Media on Students' Learning Outcomes Materials for Organizational System of Life Class VII SMPN 15 Bulukumba - A. Ardilla; Ainul Uyuni Taufiq; Hamansah (Al-AHYA: Jurnal Pendidikan Biologi, 2022)
This study aims to determine the effect of the engklek game on student learning outcomes on the material of life organization systems for class VII SMPN 15 Bulukumba. This study included a quasi-experimental design using a non-equivalent pretest posttest kontrol group design. The population in this study were all seventh grade students of SMPN 15 Bulukumba which consisted of 4 classes. The sampling technique in this study was using purposive sampling method, the experimental class was class VII A with 22 students and the kontrol class was class VII B with 22 students. The research instrument was in the form of a learning outcome test consisting of 20 multiple choice questions. The data analysis technique used descriptive statistics and inferential statistics. The results showed that students who were taught using game media had an average learning outcome of 63.13. Meanwhile, students who were taught without using the Fan-N-Pick type of cooperative learning model had an average learning outcome of 39.86. The results of inferential statistical analysis obtained a sign value for learning outcomes of 0.011, this value indicates that sign < = 0.011 <0.05 so H0 is rejected and H1 is accepted. Based on the results of the analysis, it can be concluded that the application of the engklek game media has an effect on student learning outcomes in the material of life organization sistems for class VII SMPN 15 Bulukumba.